READING HABIT, VOCABULARY MASTERY AND READING COMPREHENSION OF SECONDARY SCHOOL STUDENTS OF PATRA MANDIRI - Nana Lusianah (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The aims of this study were to find out whether or not there were significant correlations between reading habit and reading comprehension, between the aspects of reading habit and reading comprehension, between vocabulary mastery and reading comprehension and between the predictor variables (Reading Habit and Vocabulary Mastery) and criterion variable (Reading Comprehension). It was also aimed to see whether or not the aspects of reading habit and vocabulary mastery gave significant contributions to students' reading comprehension. Four hundred twenty eight students were selected as the sample by using stratified random sampling. The data were collected by using a reading habit questionnaire, a vocabulary test, and a reading test. Spearman's Rank-Order Correlation and multiple regression analyses were applied to analyze the data. The results of this study showed that there was a significant correlation (r=0.097) between reading habit and reading comprehension that was categorized as low correlation. There was only one aspect of reading habit (reading attitude) had a significant correlation (r=0.095) to reading comprehension; there was also a significant correlation (r=0.386) between vocabulary mastery and reading comprehension and between predictor variables (Reading Habit and Vocabulary Mastery) and criterion variable (Reading Comprehension). The results of this study also showed that reading habit and vocabulary mastery gave contribution (18.1%) to students' reading comprehension. In conclusion, there were significant correlations among reading habit, vocabulary mastery and reading comprehension of secondary school students of Patra Mandiri. Keywords: reading habit, vocabulary mastery, reading comprehension, secondary school students